(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
The generalization of all theories about character defining, giving information about the basic base concepts and some classifications of semiology or semiology, recognizing the word as either a kind of sign and highlighting its semiotic significance in linguistics